Climate induced vulnerability to poverty among smallholder farmers: Evidence from Malawi. (March 2021) - Maganga, Assa M.; Chiwaula, Levison; Kambewa, Patrick
Highlights: Droughts and floods exacerbate poverty vulnerability in rain-fed agricultural-based economy. Floods increase the probability of staying in poverty and pulling the non-poor into poverty trap. The impacts of climate related shocks are strong in the short term. The nexus between climate shocks and poverty has implications for livelihoods and sustainable agricultural development. Strategic climate adaptive capacity of farmers is strengthened through livestock ownership. Abstract: Assessment of farmers' climate change induced vulnerability is an important step for enhancing the understanding and decision-making to reduce such vulnerability. Using panel version of Malawi Living Standards Measurement Survey data of 2010, 2013 and 2016, this paper examines the magnitude of climate induced vulnerability to expected poverty among farming households and how climate change relates to ex-post poverty and poverty transition. We find that vulnerability is strongly associated with short-run climate stresses and less so with the long-run climate related shocks. The effects of vulnerability on actual poverty lessen with time in the long run. Similarly, climate related stresses worsen the welfare of farming households. Droughts, floods and irregular rainfall exacerbates poverty with droughts showing the greatest impact on farmers welfare loss, followed by floods. The study underscores the importance of livestock, in buffering against poverty through serving a safety net, and off-farm income-generating activities. This suggests that the inclusion of livestock in shaping of climate management policies for farmers is crucial.